TINJAUAN ATAS PROSEDUR PENAGIHAN PIUTANG USAHA PADA PT SISTELINDO MITRALINTAS - Indah Yuliana (2022)
This Final Project Report describes the procedures for collecting receivables at PT Sistelindo Mitra Lintas. Receivables are transactions that arise due to sales on credit during the company's operational activities. Receivable collection procedure is a method used by a company regarding the method or steps taken by the company before collecting the debtor. PT Sistelindo Mitra Lintas is a company in Indonesia that is engaged in the telecommunications sector that has been well integrated with customers in both national and international areas. In collecting receivables at PT Sistelindo Mitralintas it requires several related documents such as service contracts and minutes. In addition, the receivable collection flow at PT Sistelindo Mitra Lintas involves several parties, the parties involved include the operations section, administration section, finance section, and accounting section. The collection of receivables at PT Sistelindo Mitra Lintas has been structured because it has used a fairly good accounting information system, so that PT Sistelindo Mitra Lintas can minimize the occurrence of fraud.